What Human Planning Can Tell Us About Animal Planning: An Empirical Case - Martin-Ordas, Gema (Frontiers in Psychology, 2020)
The ability to think about and plan for the future is a critical cognitive skill for our daily life. There is ongoing debate about whether other animals possess future thinking. Part of the difficulty in resolving this debate is that there is not a definite methodology that allow us to conclude that animals (and human children) are truly thinking about a future event. Research with humans—both children and adults- will benefit the field of comparative psychology by providing information about the range of humans’ responses when they are faced with problems similar to those presented to other animals. Inspired by a problem that chimpanzees experienced in the wild, children of 4 and 5 years of age and young adults were presented with a situation in which they were expected to select two tools in order to obtain a reward. More older children than 4 years old successfully obtained the reward. Adults also succeeded at solving the problem. However, both children and adults struggled to select the two correct tools before any tool-use action was executed. While children’s performance is discussed in the context of temporal components required to envisage future events, adults’ performance is interpreted in the context of cognitive effort. These findings link developmental and adult cognition with comparative psychology.